1969
DOI: 10.1037/h0020058
|View full text |Cite
|
Sign up to set email alerts
|

Response Latency as a Function of Training Method, Information Level, Acquisition, and Overlearning.

Abstract: Response latency was studied as a measure of associative strength or degree of learning and as a possible basis for instructional decision making in computer-assisted instruction. Latency was investigated in a paired-associate task as a function of training procedure (a comparison of the anticipation and recall paradigms) and information transmission requirements (a comparison of two, four, and eight response alternatives to an eight-item stimulus list) during both acquisition and overlearning. The magnitude a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It is well established that repeated practice of words leads to faster word recognition based on word-specific knowledge (e.g. Judd & Glaser, 1969;Lemoine, Levy, & Hutchinson, 1993;Samuels, 1997), but not to transfer to unpractised words, even when they share sublexical units (Thaler, Ebner, Wimmer & Landerl, 2004). Van den Bosch, van Bon and Schreuder (1995) demonstrated that (some) generalization could be achieved when the phonological recoding process was continuously stimulated by presenting new pseudowords time and again.…”
Section: Introductionmentioning
confidence: 97%
“…It is well established that repeated practice of words leads to faster word recognition based on word-specific knowledge (e.g. Judd & Glaser, 1969;Lemoine, Levy, & Hutchinson, 1993;Samuels, 1997), but not to transfer to unpractised words, even when they share sublexical units (Thaler, Ebner, Wimmer & Landerl, 2004). Van den Bosch, van Bon and Schreuder (1995) demonstrated that (some) generalization could be achieved when the phonological recoding process was continuously stimulated by presenting new pseudowords time and again.…”
Section: Introductionmentioning
confidence: 97%
“…In this respect, fluency could nevertheless be useful, both as a measure of the degree of learning that occurs beyond a 100% accuracy level and as a criterion to decide when practice should be stopped. Judd and Glaser (1969) made a similar proposal in their studies of the effect of overlearning on response latency. They argued that response latency could serve as an accurate measure of learning progress and could thus be used for instructional decision making, especially in situations where response accuracy was high.…”
Section: Precision Teaching and Fluency Researchmentioning
confidence: 76%
“…However, because (a) fluency training always involves practicing beyond initial mastery, and (b) repeated practice is accompanied by a decrease in response latency ( Judd & Glaser, 1969;Newell & Rosebloom, 1981), it becomes difficult to ascertain whether the observed benefits of fluency training are caused by the achieved fluency level or simply by the amount of additional practice needed to establish it. This situation has led Dougherty and Johnson (1996) to suggest that fluency might not be distinguishable from overlearning or automaticity.…”
Section: Precision Teaching and Fluency Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that it is the increase in information transmission with three alternatives over two alternatives that reduces the probability of giving the same alternative consistently. In paired-associate learning an increase in information transmission increases the latency of responding (Judd & Glaser, 1969). It is possible that in this task an increase in the time necessary to process the material is responsible for the decrease in c. Confirmation of this hypothesis must await experimentation in which the latencies are obtained.…”
Section: Discussionmentioning
confidence: 99%